The Implementation of Environmental-Based Occupational Health and Safety Management System (SMK3L) Using Hazard Identification, Risk Assessment, and Risk Control (HIRARC) Method on the Drainage Project in the City of Samarinda - Rusli, Rusli; Zulkarnain , Isnaini; Agustina, Fitriyati (JSE Journal of Science and Engineering, 2024)
The Semani Drainage Works Project (Sentosa-Remaja-A. Yani) is an initiative in the development of waterways in Samarinda City. The large-scale development and the high level of risk of work accidents on the project require close monitoring of the Environment-Based Occupational Health and Safety Management System (SMK3L). This study aims to identify potential hazards and analyze the risks of potential hazards and design improvements to reduce the impact of risks using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. The result of this research is the discovery of 117 potential hazards on projects located in three different locations. Where the drainage work on Jalan Pemuda 1 has a low risk level (low) of 21%, a moderate risk level (moderate) of 38%, a high risk level (high) of 41%, and an extreme risk level (extreme) of 0%. For drainage work on the D.I. Pandjaitan road, it has a low risk level (low) of 18%, a moderate risk level (moderate) of 31%, a high risk level (high) of 51%, and an extreme risk level (extreme) of 0%. And for the level of risk in drainage work on Sentosa road has a low risk level (low) of 18%, a moderate risk level (moderate) of 36%, a high risk level (high) of 46%, and an extreme risk level (extreme) of 0%. Risk control or improvement design focuses on Engineering Control and administration as well as Personal Protective Equipment (PPE).